GENETIC DETERMINANTS OF SLEEP APNEA SYNDROME: A REVIEW OF CONTEMPORARY DATA - O. Yu. Shaydyuk; M. A. Kudinova; E. O. Taratukhin (Российский кардиологический журнал, 2015)
The article is on some contemporary data about genetic specifics of patients with sleep apnea syndrome. The data discussed is concerned on either adult and newborn subjects with the syndrome.